2010
DOI: 10.2147/cia.s9664
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and management of nutrition in older people and its importance to health

Abstract: Abstract:Nutrition is an important element of health in the older population and affects the aging process. The prevalence of malnutrition is increasing in this population and is associated with a decline in: functional status, impaired muscle function, decreased bone mass, immune dysfunction, anemia, reduced cognitive function, poor wound healing, delayed recovery from surgery, higher hospital readmission rates, and mortality. Older people often have reduced appetite and energy expenditure, which, coupled wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
109
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 252 publications
(150 citation statements)
references
References 87 publications
1
109
0
2
Order By: Relevance
“…This was frustrating to them, as they felt that this patient group, who were still living at home, could perhaps benefit most from preventive care. If inadequate diet and malnutrition could be avoided, it might be possible to prevent health decline and also reduce hospital admission rates (Ahmed & Haboubi 2010). Furthermore, it has been shown that those with risk for malnutrition benefit more from intervention than those rated as malnourished (Lee et al 2009), indicating that timeous actions in the community may help to reduce the high rate of undernutrition in nursing homes (Naseer et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…This was frustrating to them, as they felt that this patient group, who were still living at home, could perhaps benefit most from preventive care. If inadequate diet and malnutrition could be avoided, it might be possible to prevent health decline and also reduce hospital admission rates (Ahmed & Haboubi 2010). Furthermore, it has been shown that those with risk for malnutrition benefit more from intervention than those rated as malnourished (Lee et al 2009), indicating that timeous actions in the community may help to reduce the high rate of undernutrition in nursing homes (Naseer et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Satisfying the decreased needs for energy may pose some risk of nonbalancing mineral elements or vitamins. In such cases, it is necessary to change the proportions of consumed products, for example, high-fat content and sugar products should be replaced by skimmed dairy products, lean meat, as well as vegetables and fruits (Ahmed & Haboubi, 2010).…”
Section: Aging-related Physiological Changes That Might Affect Functimentioning
confidence: 99%
“…Aging is often associated with the decline of nutritional status in both hospitalized (Forster & Gariballa, 2005) and homebound older adults (Ahmed & Haboubi, 2010;Lee, Hwang, Artan, Jeong, & Lee, 2015;Leslie & Hankey, 2015). Despite various attempts to define the risk of underlying factors such as illness, improper nourishment, financial difficulties, and polytherapy, there is a lack of unambiguous standards to diagnose undernourishment, and the prevailing number of existing screening methods has no adequate specificity and sensitivity (Poggiano et al, 2017).…”
Section: Aging-related Physiological Changes That Might Affect Functimentioning
confidence: 99%
“…Mit dem Alter steigt auch das Risiko für Mangelernährung. Diese geht mit eingeschränkter Muskelfunktionalität, Verlust an Knochenmasse, Anfälligkeit des Immunsystems, Anämien, reduzierter kognitiver Funktion, verschlechterter Wundheilung, verzögerter Genesung nach Operation, längeren Krankenhausaufenthalten und letztendlich gesteigerter Mortalität einher [6]. Dabei ist anzumerken, dass dem Thema Mangelernährung gerade im klinischen Alltag zu wenig Beachtung geschenkt wird.…”
Section: ) Wurde Durchgeführt Zur Einschätzung Der Relevanzunclassified